Advected glacial seawater preserved in the subsurface of the Maldives carbonate edifice. (15th July 2019) - Blättler, Clara L.; Higgins, John A.; Swart, Peter K.
Abstract: Analysis of both conservative and reactive geochemical tracers in pore fluids extracted from sediment cores from the Maldives Inner Sea reveal extensive interstitial water masses whose origins lie in glacial intermediate water advected laterally through the Maldives carbonate edifice. These drillcores, recovered during Expedition 359 of the International Ocean Discovery Program, penetrate late Oligocene to Recent sediments including carbonate platform, slope, pelagic, and drift facies. Combined shipboard and shore-based analyses of the pore fluids show linearly co-varying changes in the concentration of chloride and δ 18 O and δ D values of 25 mM, 1.2‰, and 9‰, respectively. Additionally, pore fluid strontium concentrations and calcium isotope ratios are strongly anti-correlated with each other. Multiple reversals in these geochemical properties with depth indicate the existence of several distinct interstitial water masses. These variations are interpreted as representing the different ages and reactive histories of young (Pleistocene and Holocene) waters advecting through the much older sedimentary formations. In particular, the elevated chloride concentrations and water isotope ratios suggest that seawater from the Last Glacial Maximum is preserved in the subsurface, where it occupies over 400 m of the sediment column within Mid- to Late Miocene sediments. These pore fluids constrain the properties of an intermediate depth glacial water mass that had higher salinity and δ 18 O and δ D values than the average glacial ocean. This system represents a unique archive yielding the most direct observations of glacial seawater to date, as well as a demonstration of the long-lasting potential for water-rock interaction in carbonate platform systems.